CLINICAL EFFICACY OF LOOP DIURETIC TORASEMIDE IN TREATMENT OF PATIENTS WITH CHRONIC HEART FAILURE. RESULTS OF KAZAKHSTAN MULTICENTER STUDY "POET" - S. F. Berkinbaev; G. A. Dzhunusbekova; A. K. Isabekova (Рациональная фармакотерапия в кардиологии)
Aim. To study the efficacy of loop diuretic torasemide compared with furosemide consisting of combination therapy in patients with chronic heart failure (CHF).Material and methods. Inpatient and outpatient patients (n=136; 80 men and 56 women) with CHF class 2-3 (NYHA) living in different regions of Kazakhstan were included into the study.Results. More pronounced decrease in edema syndrome, significant decrease in the rate of maladaptive myocardial remodeling, increase in systolic function by 8.2%, improving quality of life by 30.1% took place during combination therapy including loop diuretic torasemide compared with furosemide.Conclusion. The loop diuretic torasemide consisting of combination therapy has a positive effect on myocardial remodeling and improves quality of life in patients with CHF class 2-3 (NYHA).